(3Mbhb GdeSGge GdeQJHWI HEOGQI TQcI GdeSGgeI h GdQbGHI YdjgG (B/ s - (3SGQI CMeO MeOGf YHO GdQGRbs; (3Ndjd ajcJhQ JGOQS s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2012)
(3JfGhdJ GdOQGSI ehVhY Mbhb GdeSGge GdeQJHWI HEOGQI TQcI GdeSGgeI h GdQbGHI YdjgG ai GdbGfhf GdeUQj eY GdebGQfI HCMcGe GdbGfhf GdaQfSj h HYV GdJTQjYGJ GdeYehd HgG ai HYV GdOhd GdYQHjI h ef NdGd Jdc GdOQGSI bO GJVM dfG eOi GdCgejI GdJj jJeJY HgG gPG GdehVhY ai eLGd GdTQcGJ ShGA ai eUQ Ch ai GdJTQjYGJ GdCNQi h HGdQZe ef GdedGMXGJ GdJj GJVMJ dfG ef NdGd gPg GdOQGSI GdJj JDNP Ydi JfXje GdeTQY GdeUQj dHYV gPg GdMbhb EdG Cfg gfGc Yed jJe HGSJeQGQ dJUMjM eSGQ gPG GdJfXje h MeGjI GdeSGgejf HTcd edMhXs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2012.s
(3HHdjhLQGajI(B: (3UaMI (B228-236s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3TQcI GdeSGgeIs; (3GdeSGges; (3GdGYdGe hGdYdGfjIs; (3GdeQGbHs; (3GdLeYjI GdYehejIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs